Understanding Attitude towards Reusable Bag: Its Antecedents and Consequences - Ayu Ekasari; Fatik Rahayu; Afif Diamanta (International Journal of Science and Society, 2021)
Environmental damage caused by individuals and household activities has increased the need to foster people to act pro-environmentally. Indonesia is an emerging country that has committed to encourage people to use reusable bag that can help reducing plastic waste and preserve the environment. However, people’s willingness to use reusable bag is far from being expected. This research aims to examine the internal and external factors as well as consequences of attitude towards using reusable bag. The questionnaire survey was administered to 300 respondents that have ever seen and understood the usability of reusable bag. Structural equation modelling was then used to analyse the data. The findings reveal that environmental knowledge, lifestyle of health and sustainability as well as moral norms do influence attitude towards reusable bag which leads to intention to use it, which is consistent with some previous studies. The study also finds that people’s attitude is not influenced by social influence from others. Managerial implications are given to the policy maker and retailers to promote reusable bag. To the best of the authors’ knowledge, no study has been conducted to integrate the external and internal factors of attitudes towards reusable bag and predicts the intention to use it. Future studies needs to test the model to other pro environmental behaviour and to conduct a cross-cultural study regarding it.